Primary Cilia in Hepatic Biliary Hyperplasia: Implications for Liver Diseases - Pant, Kishor; Peixoto, Estanislao; Gradilone, Sergio A. (Seminars in Liver Disease, 2025)
Primary cilia, hair-like projections on the surface of various cell types, play crucial roles in sensing and regulating environmental cues within the liver, particularly among cholangiocytes. These structures detect changes in bile composition, flow, and other biochemical signals, integrating this information to modulate cellular processes. Dysfunction in cholangiocyte cilia—whether due to structural abnormalities or genetic mutations—has been linked to an array of cholangiopathies and ciliopathies. These include conditions such as biliary atresia, cholangiocarcinoma, primary sclerosing cholangitis, and polycystic liver diseases, each with distinct clinical phenotypes influenced by impaired ciliary function. Given the complexity of the ciliary proteome and its role in cellular signaling, including the Hedgehog, Wnt, and TGR5 pathways, ciliary dysfunction disrupts essential signaling cascades, thus driving disease progression. While over 40 gene mutations are associated with ciliopathic features, there may be additional contributors within the expansive ciliary proteome. This study synthesizes current knowledge on cholangiocyte cilia, emphasizing their mechanistic role in liver disease, and highlights emerging therapeutic strategies aimed at restoring ciliary function. In conclusion, ciliotherapies are proposed as a promising approach for addressing cholangiopathies, with the potential to shift the current therapeutic landscape.
Keywords: primary cilia; cholangiocyte; ciliopathy; polycystic liver diseases; primary sclerosing cholangitis; cholangiocarcinoma; ciliotherapies